2011
DOI: 10.1111/j.1475-3995.2011.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective 0-1 integer programming for the use of sugarcane residual biomass in energy cogeneration

Abstract: It is well known that Brazil is the largest producer of sugarcane in the world. Nevertheless, a great concern exists about the crop system used, because the most common practice is manual harvesting with prior straw burning. The Brazilian authorities have approved a law prohibiting the burning of sugarcane crop residue before harvesting. However, mechanized harvesting creates the new problem of having to deal with the residue. Many studies have indeed proposed the use of this residue as an energy source. A maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…The main decisions to be made at the time of planting are related to: what is the best time to plant, which sugarcane varieties will be planted, and how to estimate what will be obtained when the plant is ready for harvest. Among the papers selected for this study, seven were found proposing mathematical optimization models to represent decisions associated with the planting time (Florentino and Sartori, 2003;Sartori and Florentino, 2007;Florentino et al, 2008;Colin, 2009;Florentino et al, 2011;Florentino and Pato, 2014;Lima et al, 2017). Florentino et al (2008Florentino et al ( , 2011, Florentino and Pato (2014), Lima et al (2017), and Sartori and Florentino (2007) present binary linear optimization models to select the varieties for planting.…”
Section: Plantingmentioning
confidence: 99%
“…The main decisions to be made at the time of planting are related to: what is the best time to plant, which sugarcane varieties will be planted, and how to estimate what will be obtained when the plant is ready for harvest. Among the papers selected for this study, seven were found proposing mathematical optimization models to represent decisions associated with the planting time (Florentino and Sartori, 2003;Sartori and Florentino, 2007;Florentino et al, 2008;Colin, 2009;Florentino et al, 2011;Florentino and Pato, 2014;Lima et al, 2017). Florentino et al (2008Florentino et al ( , 2011, Florentino and Pato (2014), Lima et al (2017), and Sartori and Florentino (2007) present binary linear optimization models to select the varieties for planting.…”
Section: Plantingmentioning
confidence: 99%
“…2020), quienes proponen modificaciones y ajustes en los procesos industriales para obtener mayores eficiencias en la producción de biocombustibles, reduciendo el nivel de emisiones equivalentes. De igual manera, algunos autores han propuesto incrementar la producción de biocombustibles y energía por cogeneración eléctrica del bagazo, considerando la recolección de la biomasa del campo (residuo de cosecha), así como el residuo de la caña de azúcar (luego de la extracción del jugo) (Mishoe et al, 1979;Sartori et al, 2001;de Oliveira Florentino & Pereira Sartori, 2003;De Oliveira Florentino et al, 2011;de Oliveira Florentino & Pato, 2014).…”
Section: Perspectiva Sostenible En Las Asc En La Caña De Azúcarunclassified
“…A través de información climática, el modelo propuesto en (Bezuidenhout & Singels, 2007b) fue testeado, también, se simulo la producción de los Con el objetivo de maximizar la producción de caña de azúcar, proponen un modelo de simulaciónoptimización el cual permite recomendar, variedad que se debe cultiva, fechas de siembra y cosecha para una temporada de cosecha De Oliveira Florentino et al (2011) x ---x ---p Proponen un modelo para la cogeneración de energía eléctrica usando residuos de la cosecha de caña de azúcar; encontrando un plan de cosecha que balancea el costo de la energía requerida y la generada x ----x x x p Desde la perspectiva sostenible, los autores proponen un modelo para la evaluación de la SC de biocombustibles. No considera aspectos de la ASC de Oliveira Florentino et al (2018) x x -x x x --v Proponen un modelo de optimización y una metaheurística para programar la cosecha, considerando el periodo de maduración y la fecha de siembra, así como, los intereses del ingenio…”
Section: Modelounclassified
“…Some authors, like those of reference [25], propose a multi-objective integer linear programming optimization model to choose sugarcane varieties to minimize costs in the use of crop residue and simultaneously maximize the energy balance in such a process. In that paper, the authors considered different logistics costs.…”
Section: Literature Review-bioenergy Supply Chain Optimizationmentioning
confidence: 99%